Successful implementation of the 360° video teaching approach to promote immersion and theory-practice transfer in social work - Averbeck, Felix; Utesch, Till (Frontiers in Education, 2025)
This study examines the use of 360° videos in social work education, an innovative teaching approach developed at the University of Applied Sciences in Münster and tested at the University of Applied Sciences in Fulda. The research aims to evaluate the potential of 360° videos for enhancing immersion, promoting theory-practice transfer, and assessing the approach’s adaptability to different institutional settings. Findings indicate that 360° videos significantly increase students’ sense of presence and flow, fostering deeper engagement and understanding of the material. A comparative analysis of the implementations at Münster and Fulda confirms the reproducibility of these effects across different contexts. The study addresses the key factors required for successfully adopting this teaching method at other universities. Future research should explore the long-term impact of 360° videos on teaching quality and learning outcomes, further leveraging immersive technologies to strengthen the integration of theory into practice.